Effect of nanoclay on the microstructure and the properties of Thermoplastic Natural Rubber (TPNR)/OMMT nanocomposites - Hassan, Noor Azlina; Haji Ahmad, Sahrim; Rasid, Rozaidi (Sage Publications, 2012)
Thermoplastic natural rubber (TPNR)/organo-montmorillonite (OMMT) nanocomposites were prepared by melt blending method with the optimum mixing parameters (1408C, 100 rpm, 12 min) using internal mixer (Haake 600 P). The aim of this study is to determine the effects of OMMT on the microstructure and properties of TPNR with and without coupling agent(maleic anhydride grafted polyethylene, MA-PE). In this study, tensile test was performed to investigate the optimum system of TPNR/OMMT nanocomposites within 2–8wt% filler content. It revealed that the optimum loading of OMMT was at 4 wt%. Furthermore, this system was studied with the incorporation of MA-PE(3–15 wt%). The microstructure of the nanocomposites was characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The XRD and TEM results exhibited that a combination of intercalated and exfoliated structure was formed in the composites. The thermal stability and crystallization of the nanocomposites were further investigated using differential scanning calorimetry(DSC) and thermal gravimetric analysis (TGA). The thermal stability of the nanocomposites, characterized by the initial decomposition temperatures, was substantially improved compared with that of the neat TPNR. The DSC results show that the crystallization temperature of nanocomposites was increased compared with the neat TPNR. The Tg of TPNR was lowered by the incorporation of the OMMT.